The future of ICT-related small and medium sized enterprises in remote Scottish Islands - Greller, Wolfgang; Mackay, Mary (2002)
Wolfgang Greller and Mary MacKay examine the weaknesses, strengths, adaptability and sustainability of ICT-related companies in the highlands and the western isles of Scotland, among the most remote and sparsely populated regions on the periphery of western Europe. - Reproduced.
Keywords: Communication technology; Education; Information technology